Penerapan Algoritma Prophet Facebook untuk Memprediksi Jumlah Calon Mahasiswa Baru - Putri, Evydian Rosa; Kristianto, Budhi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
According to the data set of the Central Statistics Agency of the Ministry of Education, Culture, Research, and Technology, the number of students in Indonesia in 2021 was 8.96 million, and in 2022 the number of students increased to 9.32 million. Of the 9.32 million students in Indonesia, 4.49 million students pursue higher education at private universities (Ministry of Education, Culture, Research and Technology, 2023). This was followed by the number of universities which also increased, in 2022 reaching 4,004, up 0.73% compared to the previous year (BPS, 2023). In this case, XYZ University is affected by changes in the number of prospective new students, especially at the Faculty of Information Technology. The rapidly developing technology of this era triggers prospective students to learn about Information Technology. Thus, a prediction is carried out to help the Faculty of Information Technology of XYZ University know the number of enthusiasts for each study program and help arrange their resources. The prediction results of each study program show a deviation 10 compared to the actual data and an average RMSE of 0.44578.